An Analysis of Perempuan Berkalung Sorban Novel: Feminist Perspective - Aryanika, Septa (Universitas Islam Negeri Raden Intan Lampung, 2016)
In the patriarchy society, women are viewed to be the second class under men. This study aims at knowing how feminism in Perempuan Berkalung Sorban novel by Abidah El Khalieqy. The purpose of this study are to: 1) describe feminism in novel Perempuan Berkalung Sorban novel, 2) know the groups of feminism in Perempuan Berkalung Sorban novel. This research was qualitative descriptive research method. The results showed: 1) the feminism in Perempuan Berkalung Sorban novel describe a woman’ stuggle in getting her existence and rights as a independent human being, and 2) this novel contents liberal feminism and radical feminism.